Pembelajaran Beyond Center and Circle Time (BCCT) Berbasis Bahasa Inggris - Amalia, Taranindya Zulhi (Indonesian Journal of Islamic Early Childhood Education, 2018)
Abstract Three objectives of this research are: 1) to know English learning, 2) to describe English-based BCCT, and 3) to confirm supporting and obstacle factors of English-based BCCT at TKIT Abu Bakar Ash Shidiq Margorejo Pati and to find the solutions. Primary data sources of this field research applied to qualitative descriptive approach are the headmaster of TKIT, Sie curriculum, ustadzah-ustadzah of BCCT, and parents. While the secondary data are a source relevant to the learning of English and BCCT. They are generated by moderate participatory observation, semi-structured interview, and documentation. Accordingly, the results were: 1) English Lesson reffered to themes and subthemes containing local wisdom values in the 2013 early childhood education curriculum and were supported by triple language dictionary, 2). English based BCCT in some centers did vocabulary repetition through songs. Each center applied foothold before playing(warms-up), playing (main activities), and after playing (closing activities) in moving classes, and 3) the supporting factors were adequate curriculum, appropriate center-class design, adequate tools, creative teachers, and supporting parents at home. While the obstacles were minimum time allotment of English in the curriculum, minimum English vocabulary introduction, in the introduction of English vocabulary, less consistency of English in the themes, and less focused learners in learning. Finally, the solutions were to allocate English starting from daily lesson plans, have English center and circle time, and develop routine language agenda. Keywords: Beyond Center & Circle Time (BCCT), English, Early Childhood Tiga tujuan penelitian ini untuk: 1) mengetahui pembelajaran Bahasa Inggris, 2) mendeskripsikan pembelajaran Beyond Center and Circle Time (BCCT) berbasis Bahasa Inggris, dan 3) mengklasifikasikan faktor pendukung dan penghambat pembelajaran Beyond Center and Circle Time (BCCT) berbasis Bahasa Inggris di TKIT Abu Bakar Ash Shidiq Margorejo Pati serta menemukan solusinya. Sumber data primer penelitian lapangan ini diterapkan pada pendekatan deskriptif kualitatif yaitu kepala TKIT, sie kurikulum, ustadzah-ustadzah BCCT, dan orang tua. Sedangkan data sekunder adalah sumber yang relevan dengan pembelajaran Bahasa Inggris dan BCCT. Teknik pengumpulan datanya adalah observasi partisipatif moderat, wawancara semi-terstruktur, dan dokumentasi. Hasil penelitian ini menunjukkan: 1) Pelajaran Bahasa Inggris mengacu pada tema dan sub-tema yang mengandung nilai-nilai kearifan lokal dalam kurikulum PAUD dan didukung oleh kamus tiga bahasa, 2). BCCT berbahasa Inggris di beberapa sentra melakukan pengulangan kosakata melalui lagu-lagu. Setiap sentra menerapkan pijakan sebelum bermain saat main, dan setelah bermain dalam moving class, dan 3) faktor pendukung adalah kurikulum yang memadai, desain sentra yang sesuai,dan dukungan orang tua di rumah. Sedangkan hambatannya adalah alokasi waktu  bahasa Inggris dalam kurikulum dan pengenalan kosakata bahasa Inggris minimum, pemberdayaan guru belum maksimal dalam pengenalan kosakata Bahasa Inggris, konsistensi pembelajaran Bahasa Inggris dalam tema-tema kurang, serta fokus peserta didik kurang dalam pembelajaran. Solusinya yakni alokasi waktu Bahasa Inggris mulai dari RPPH, pengadaan sentra Bahasa Inggris, serta agenda rutin pengembangannya.                              Kata kunci: Beyond Center & Circle Time (BCCT),bahasa Inggris, anak usia dini